Toxic Work Environment Among Cross-Generational Employees - Satwika, Pratista Arya; Kusumawati, Rafika Nur (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Toxic work environments not only negatively impact the mental and physical well-being of employees but also affect employee productivity and retention. A cross-generational perspective is crucial to providing more comprehensive insights and helping organizations create a healthy work culture. This study aimed to describe the toxic work environment perceived by cross-generational employees and the demographic variables that influence it. The quantitative research used a convenience sampling technique. The sample consisted of 783 Indonesians aged 19 to 60 years who had worked for at least 1 year. The study examined the perceived toxic work environment using descriptive statistics. In addition, researchers also used Mann-Whitney U and Kruskal-Wallis statistical analyses to see the differences based on the demographic data collected. The results found that the majority of the toxic work environments perceived by employees were in the low category (91%). The analysis also showed that differences in generation, type of work, and length of service affect the toxic work environment felt by employees. The toxic work environment is more prevalent among Generation Z, employees who work in the private sector, and those who have worked for 5 years or less.